Testicular fibroma of gonadal stromal origin with minor sex cord elements, presenting with hydrocele - Saikat Datta; Soumit Dey; Sumana Mukherjee; Prabir Chandra Paul; Aparna Bhattacharyya; Sukdeb Biswas; Balaram Tudu (Rare Tumors, 2013)
Testicular fibroma of gonadal stromal origin is a rare benign tumor of testis which usually presents as a slow growing testicular mass. Only 25 cases of testicular fibroma have been reported in the literature. Presence of minor sex cord elements in this tumor is even rarer. We report a case of testicular fibroma with minor sex cord elements that involved almost the entire testis and tunica vaginalis. The patient presented with hydrocele, a rare presentation for this entity. The rarity of the diagnosis and the clinical presentation prompted this case report.